2017
DOI: 10.1007/s00604-017-2597-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioimaging of metallothioneins in ocular tissue sections by laser ablation-ICP-MS using bioconjugated gold nanoclusters as specific tags

Abstract: An immunohistochemical method is described to visualize the distribution of metallothioneins 1/2 (MT 1/2) and metallothionein 3 (MT 3) in human ocular tissue. It is making use of (a) antibodies conjugated to gold nanoclusters (AuNCs) acting as labels, and (b) laser ablation (LA) coupled to inductively coupled plasma - mass spectrometry (ICP-MS). Water-soluble fluorescent AuNCs (with an average size of 2.7 nm) were synthesized and then conjugated to antibody by carbodiimide coupling. The surface of the modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 32 publications
(36 reference statements)
4
33
0
Order By: Relevance
“…Although several studies can be found nowadays in the literature related to the imaging of biomolecules by LA-ICP-MS, most of them only collect qualitative distributions of sought proteins. In this context, we have recently proposed the use of small metal nanoclusters (NCs) with fluorescent properties as elemental labels for specific and absolute quantitative imaging of proteins in biological tissues by LA-ICP-MS [21,22]; considering that each NC has several hundreds of metal atoms, a high signal amplification in LA-ICP-MS measurements can be achieved. Therefore, these metal NCs offer possibilities for multimodal imaging (through fluorescence and MS analysis) in the same tissue section.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies can be found nowadays in the literature related to the imaging of biomolecules by LA-ICP-MS, most of them only collect qualitative distributions of sought proteins. In this context, we have recently proposed the use of small metal nanoclusters (NCs) with fluorescent properties as elemental labels for specific and absolute quantitative imaging of proteins in biological tissues by LA-ICP-MS [21,22]; considering that each NC has several hundreds of metal atoms, a high signal amplification in LA-ICP-MS measurements can be achieved. Therefore, these metal NCs offer possibilities for multimodal imaging (through fluorescence and MS analysis) in the same tissue section.…”
Section: Introductionmentioning
confidence: 99%
“…10 A major difficulty for both of these imaging approaches is the square relationship between signal intensity and spot size, which limits the practical spot size for quadrupolebased instruments to approximately 4 to 10 μm. 5,11 Below this, there is not enough material in each sampling event for detection.…”
Section: Introductionmentioning
confidence: 99%
“…AuNPs can act as perfect contrast agents for imaging, in addition to QDs, and several authors have used AuNPs for imaging eye cancers over the past few years [ 82 ]. For example, Cruz-Alonso et al described an immunohistochemical approach for visualizing the distribution of metallothionein 3 (MT3) and metallothionein 1/2 (MT 1/2) in human ocular tissue [ 74 ]. In this methodology, Au nanocluster (AuNC)-connected antibodies are used as markers and can be coupled with ICP-MS. Water-soluble fluorescent AuNCs with an average size of 2.7 nm were prepared by carbodiimide coupling and then covalently linked to antibodies.…”
Section: The Role Of Nanotechnology In the Diagnosis Of Retinoblastomamentioning
confidence: 99%